The Choroid Plexus Is Permissive for a Preactivated Antigen-Experienced Memory B-Cell Subset in Multiple Sclerosis - Haas, Jürgen; Rudolph, Henriette; Costa, Leonardo; Faller, Simon; Libicher, Saskia; Würthwein, Cornelia; Jarius, Sven; Ishikawa, Hiroshi; Stump-Guthier, Carolin; Tenenbaum, Tobias; Schwerk, Christian; Schroten, Horst; et al. (Frontiers in Immunology, 2021)
The role of B cells in multiple sclerosis (MS) is increasingly recognized. B cells undergo compartmentalized redistribution in blood and cerebrospinal fluid (CSF) during active MS, whereby memory B cells accumulate in the CSF. While B-cell trafficking across the blood–brain barrier has been intensely investigated, cellular diapedesis through the blood–CSF barrier (BCSFB) is incompletely understood. To investigate how B cells interact with the choroid plexus to transmigrate into the CSF we isolated circulating B cells from healthy donors (HC) and MS patients, utilized an inverted cell culture filter system of human choroid plexus papilloma (HIBCPP) cells to determine transmigration rates of B-cell subsets, immunofluorescence and electron microscopy to analyze migration routes, and qRT-PCR to determine cytokines/chemokines mediating B-cell diapedesis. We also screened the transcriptome of intrathecal B cells from MS patients. We found, that spontaneous transmigration of HC- and MS-derived B cells was scant, yet increased significantly in response to B-cell specific chemokines CXCL-12/CXCL-13, was further boosted upon pre-activation and occurred via paracellular and transcellular pathways. Migrating cells exhibited upregulation of several genes involved in B-cell activation/migration and enhanced expression of chemokine receptors CXCR4/CXCR5, and were predominantly of isotype class switched memory phenotype. This antigen-experienced migratory subset displayed more pronounced chemotactic activities in MS than in HC and was retrieved in intrathecal B cells from patients with active MS. Trafficking of class-switched memory B cells was downscaled in a small cohort of natalizumab-exposed MS patients and the proportions of these phenotypes were reduced in peripheral blood yet were enriched intrathecally in patients who experienced recurrence of disease activity after withdrawal of natalizumab. Our findings highlight the relevance of the BCSFB as important gate for the entry of potentially harmful activated B cells into the CSF.